412 Is front door streaming effective at identifying COVID-19 positive patients on presentation to the paediatric emergency department?. (17th August 2022) - Nutton, Laura; Jenner, Rachel
Abstract : Aims: In response to the COVID-19 pandemic, a streaming process was implemented in the Paediatric Emergency Department (PED) to identify children thought to be at higher risk of having COVID-19. This study aimed to identify if the front door risk assessment was accurate in identifying children and young people (CYP) who were COVID-19 positive on hospital admission. Comparing with final hospital discharge diagnosis, we aimed to understand if there is efficacy in PED streaming into low and high-risk of COVID-19 groups, with separate waiting and assessment areas. Methods: Patients with positive COVID-19 PCRs tests taken in PED from 16 th October- 9 th December 2021 were selected. Policy in PED at that time was only to perform a COVID-19 PCR test on CYP being admitted to hospital. The PED triage and hospital discharge notes were reviewed retrospectively for presenting complaint and discharge diagnosis. Patients were divided into having risk factors identifiable versus no indicators if one or more of the following was present: fever, coryza, cough, breathing difficulty or low oxygen saturations, positive lateral flow or known COVID-19 household contact. The discharge diagnoses for each group were categorised as COVID-19 being the primary reason for admission, COVID-19 plus other diagnosis or other diagnosis for both groups. Results: During this 8-week period, there were 8946 PED attendances and 1104 admissions. 44 COVID-19 positive patients were identified, accounting for 4% of admissions. 1 patient was excluded due to lack of notes available. 56% (24) of the CYP who tested positive for COVID-19 had risk factors identified via the front door streaming process, versus 44% (19) without any identifiable risk factors. Of 24 patients with indicators of potential COVID-19 infection, 75% (18) had COVID-19 as main diagnosis (10 as COVID-19 only, 8 COVID-19 plus another diagnosis). Of 19 patients with no identified risk factors, 68.4% (13) had an alternative diagnosis with testing positive for SARS-CoV-2 an incidental finding. 1 patient (5.3%) had COVID-19 as the final diagnosis and 5 patients (26.3%) had COVID-19 plus other diagnoses. From all 43 patients, 24 had COVID-19 as part or all of their final diagnosis (55.8%). Testing positive for SARS-CoV-2 was an incidental finding in 19 (44.2%). Conclusion: COVID-19 positive children, present to PED with risk factors suggestive of COVID-19 infection and without. The majority of those with indicators had COVID-19 (alone or with other diagnoses) as their final diagnosis. The majority of patients without COVID-19 indicators had an alternative final diagnosis and testing positive for SARS-CoV-2 was an incidental finding. Thus, current streaming practice has limited efficacy in identifying actual presence of COVID-19 infection. There is no area of PED or clinical presentation where there is no risk of COVID-19 transmission. There is scope to review how to best use PED space alongside maintaining good infection prevention and control practices for all patients.